If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(4x-3)/12=(2x+3)/6
We move all terms to the left:
(4x-3)/12-((2x+3)/6)=0
We calculate fractions
4x/()+(-((2x+3)*12)/()=0
We calculate terms in parentheses: +(-((2x+3)*12)/(), so:We get rid of parentheses
-((2x+3)*12)/(
We multiply all the terms by the denominator
-((2x+3)*12)
We calculate terms in parentheses: -((2x+3)*12), so:We get rid of parentheses
(2x+3)*12
We multiply parentheses
24x+36
Back to the equation:
-(24x+36)
-24x-36
Back to the equation:
+(-24x-36)
4x/()-24x-36=0
We multiply all the terms by the denominator
4x-24x*()-36*()=0
We add all the numbers together, and all the variables
4x-24x*()=0
| 0.5=0.25(x+8) | | 5x²+3x+3=0 | | 2a-10=25 | | 6x-13=3(x+3) | | -35=-5(x+9) | | -7+3p=1+5p | | -3x+8+6x=71 | | 6(y+2)=-72 | | -9/x+12=-22 | | 3·x+5+x+7=3 | | 2x(10-x)=25 | | 7(x−3)=56 | | 43=34+y | | –8d=–64 | | 10x+7-4x=11 | | (x^2-6x)^2-2(x-3)^2=81 | | -6n-12=-5n-3n | | 10-4e=46 | | r/4+9=12.5 | | -11x-13=-11+16x | | 3x+20+x=18- | | -b+6b=5 | | 5(2v)+8v=234 | | v–2/3=1/3 | | f-66=4 | | 4x-3x=68+68 | | 4x+3x=68-68 | | 3(n+7)-11=-8 | | 10x+7-4x=-11 | | 172=2(11w+9) | | 3x-4x=68+68 | | O.9x=420 |